Thermal Evaluation of A Tunnel-Type Solar Dryer with Hybridization of Solar Technologies (Revista Cientifica Ingenio Magno, 2022)
Food preservation techniques have allowed seasonal foods to be consumed at any time of the year. Drying has been used for many years as a means of preservation to dry a wide variety of products. A tunnel-type solar dryer with the coupling of solar water and air heating technologies was built in the Faculty of Engineering of the Autonomous University of Campeche, located between the parallels 17°49' and 20°51' north latitude and the meridians 89°06' and 92°27' west longitude. The results of its thermal evaluation considering temperatures within the drying chamber and the climatological parameters are presented in this work. The results indicate that higher temperatures were reached with the air collector, the second-best option turned out to be the use of both technologies at the same time, and the lowest temperatures were obtained with the solar heaters of evacuated tubes, reaching 49°C, 48 °C, and 46 °C, respectively. The highest measured solar irradiation was 936.5 W/m2, the highest ambient temperature was 33.3 °C, and the lowest relative humidity was 63% at 13:00 h.
Keywords: Drying chamber, Climatic parameters, Solar dryer, Hybridization of solar technologies.